PRELIMINARY INVESTIGATION OF NUTRITIVE POTENTIAL OF UMUCASS 36 CASSAVA ROOT MEAL AS SUBSTITUTE FOR MAIZE IN BROILER DIETS - Adedokun, O O; Ojewola, G S; Ahamefule, F O (MATTER: International Journal of Science and Technology, 2018)
This experiment was carried out to evaluate the nutritive potential of UMUCASS 36 cassava root meal as a substitute for maize in broiler diets. One hundred and fifty (150) one-week old Abor Acre strains of broiler chicks were randomly assigned to 5 dietary treatments in a completely randomized design. They were replicated three times with 10 birds per replicate. The well processed cassava root meal was substituted for maize at 0, 25, 50, 75 and 100% levels and were respectively designated as diets 1, 2, 3, 4 and 5. The birds were fed and watered adlibutum for 49 days. The results show that birds fed diet 2 gave the best (P < 0.05) mean total weight gain (2033.00g), feed-to-gain ratio (2.10), least cost/kg weight gain (#286.47), and best realizable revenue (#2033.00) and gross margin (#286.47). It was also observed that UMUCASS 36 cassava root meal is rich in ether extract (4.10%), crude fibre (6.45%) and ash (7.56%).In conclusion, though the UMUCASS 36 cassava root meal is deficient in percent crude protein, it is rich in other essential nutrients and has the potential of being used as a dietary energy source in broiler diet. So, substituting maize for UMUCASS 36 cassava root meal at 25% optimized both feed and economic efficiency. It is therefore recommended as a diet of choice whenever high dressed yield and economic efficiency are reasons for broiler production. The other diets can also be used depending on the producer’s purpose and capability.